Pliocene Palaeoclimate off Southeastern Africa: Insights from IODP Expedition 361 ... - Simon, Margit (Interdisciplinary Earth Data Alliance (IEDA), 2021)
The data comprises a multi-proxy dataset of 49 samples spanning approximately the time interval from 1.8-3.9 Ma according to the currently available shipboard age model from offshore the Limpopo River, southwest Indian Ocean. Data includes major and trace element chemistry and K-Ar ages from the clay fraction (<2um), radiogenic isotope geochemistry, stable isotopes of planktonic foraminifera Globigerinoides ruber. ...